Development dimensions: a exploratory study under the perspective of the evaluation tools - Hans Michael van Bellen (Revista de Ciências da Administração : RCA, 2010)
This article explores the concept of development to focus afterwards in some tools of evaluation that work with this concept from different dimensions. In its first part the article discusses the different dimensions of development in order to present some tools that work with this concept. These tools are analyzed from several dimensions used in the evaluation process. One observes that the economic dimension is still predominant in the evaluation systems, however, significant advancements have been made in the development and application of evaluation systems that use the ecological and social dimension.